Pengembangan Media Animasi untuk Meningkatkan Pemahaman Konsep Siswa Kelas III pada Materi Siklus Hidup - Silvia Nurshobah Nasution; Ali Ismail; Sidqia Nurfadilah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The teaching of Natural Sciences in grade III elementary schools, particularly the Life Cycle topic, has predominantly relied on lecture-based delivery supported only by static illustrations in textbooks. As a result, students often struggle to grasp the sequential stages of metamorphosis and the abstract nature of living organisms' growth processes. To address this gap, the present study aimed to design an animated video medium for the Life Cycle topic, assess its feasibility, and evaluate its effectiveness in enhancing students' conceptual understanding. A research and development approach was employed, guided by the six-stage ASSURE model and supported by a one-group Pretest-Posttest pre-experimental design to determine the medium's effectiveness. Participants consisted of 29 third-grade students from Cikubang State Elementary School in Sumedang Regency, alongside one content expert, one media expert, and two teachers serving as validators. Data were gathered through interviews, expert validation questionnaires, student response questionnaires, and pretest-posttest instruments, which were subsequently analyzed using descriptive statistics, the Shapiro-Wilk normality test, the paired samples t-test, and the N-Gain test. Findings revealed that the developed animated medium was rated highly feasible, earning validation scores of 83.7% from the content expert, 83% from the media expert, and 79.69% from student responses. In terms of effectiveness, students' conceptual understanding improved markedly, with mean scores rising from 29.66 in the Pretest to 78.28 in the Posttest, accompanied by a statistically significant t-test result (p < 0.05, sig. = 0.000) and an N-Gain value of 0.67, classified as moderate and reasonably effective. These findings confirm that the animated video medium is both feasible and effective in strengthening third-grade students' conceptual understanding of the Life Cycle material.